2018
DOI: 10.1007/s10551-018-3918-y
|View full text |Cite
|
Sign up to set email alerts
|

Female CEOs and Core Earnings Quality: New Evidence on the Ethics Versus Risk-Aversion Puzzle

Abstract: The question of whether females tend to act more ethically or risk-averse compared to males is an interesting ethical puzzle. Using a large sample of US firms over the 1992-2014 period, we investigate the effect that the gender of a chief executive officer (CEO) has on earnings management using classification shifting. We find that the pre-Sarbanes-Oxley (SOX) Act period was characterized by high levels of classification shifting by both female and male CEOs, but the magnitude of such practices is, surprisingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
95
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(136 citation statements)
references
References 109 publications
9
95
0
5
Order By: Relevance
“…Female directors' level of education can affect firm's strategy towards environment and society by improving board independence and providing different perspectives of supervision (Hambrick & Mason, 1984;Hitt & Tyler, 1991;Zalata et al, 2018). Dollinger (1984) suggests that educated managers are more concerned about the external environment and they tend to be better able to deal with complex ethical issues, and that in turn can positively influence their firms' policies towards the environment and society.…”
Section: Level Of Education Of Female Directors and Environmental Permentioning
confidence: 99%
“…Female directors' level of education can affect firm's strategy towards environment and society by improving board independence and providing different perspectives of supervision (Hambrick & Mason, 1984;Hitt & Tyler, 1991;Zalata et al, 2018). Dollinger (1984) suggests that educated managers are more concerned about the external environment and they tend to be better able to deal with complex ethical issues, and that in turn can positively influence their firms' policies towards the environment and society.…”
Section: Level Of Education Of Female Directors and Environmental Permentioning
confidence: 99%
“…Given that, female CEOs are interested in participating in risky activities, while Zalata, et al, (2018) scrutinized that women are more risk-taker, which signi cantly impact on rm performance and success, especially in emerging economies (Zalata, et al, 2018). As such, the level of risk-taking by the women entrepreneur is expected to have a positive impact on performance (Zalata, et al, 2018;Wang & Poutziouris, 2010;Zhao et al, 2010). Therefore, we postulate from previous literature that women entrepreneurs are more risk-taker oriented during the decision-making process, it, in turn, has some impacts on rm performance and business success.…”
Section: Risk-taking and Women Entrepreneurs' Successmentioning
confidence: 99%
“…1 The behavioural differences between males and females have been extensively examined in the business ethics literature (Carmona et al 2018;Kelan 2008;Qi et al 2018). Gender-related studies in the accounting and auditing profession suggest that women tend to be more riskaverse and acting more ethically, but other studies found no behavioural differences between genders in high-profile jobs and leadership positions (Elmagrhi et al 2019;Lara et al 2017;Ntim 2015;Sila et al 2016;Zalata et al 2019). Despite inconsistent pieces of evidence, the existing research on gender behavioural differences appears tilted in favour of the positive implications of gender diversity for auditing and financial reporting quality (Qi et al 2018;Zalata et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Gender-related studies in the accounting and auditing profession suggest that women tend to be more riskaverse and acting more ethically, but other studies found no behavioural differences between genders in high-profile jobs and leadership positions (Elmagrhi et al 2019;Lara et al 2017;Ntim 2015;Sila et al 2016;Zalata et al 2019). Despite inconsistent pieces of evidence, the existing research on gender behavioural differences appears tilted in favour of the positive implications of gender diversity for auditing and financial reporting quality (Qi et al 2018;Zalata et al 2019). In this study, we postulate that behavioural variances between female and male in risk aversion may have significant implications for audit reporting, especially after the recent reforms.…”
Section: Introductionmentioning
confidence: 99%